2023
DOI: 10.1038/s41598-023-31107-8
|View full text |Cite
|
Sign up to set email alerts
|

An innovative traffic light recognition method using vehicular ad-hoc networks

Abstract: Car congestion is a pressing issue for everyone on the planet. Car congestion can be caused by accidents, traffic lights, rapid accelerations, deceleration, and hesitation of drivers, as well as a small low-carrying capacity road without bridges. Increasing road width and constructing roundabouts and bridges are solutions to car congestion, but the cost is significant. TLR (traffic light recognition) reduces accidents and traffic congestion caused by traffic lights (TLs). Image processing with convolutional ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…In addition, Fernando et al [14] and Huy et al [15] have also demonstrated traffic light detection and classification using YOLO. Furthermore, various methods based on Lightweight [16], PID Controller [17], Salience-Sensitive Loss [18], vehicular ad-hoc networks [19], support vector machine [20], and Adaptive Background Suppression Filter [21] have been reported for traffic light detection and classification.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Fernando et al [14] and Huy et al [15] have also demonstrated traffic light detection and classification using YOLO. Furthermore, various methods based on Lightweight [16], PID Controller [17], Salience-Sensitive Loss [18], vehicular ad-hoc networks [19], support vector machine [20], and Adaptive Background Suppression Filter [21] have been reported for traffic light detection and classification.…”
Section: Introductionmentioning
confidence: 99%